DEFORMABILITY OF ERYTHROCYTES AS A CRITERION FOR ASSESSING REACTIVE AND ADAPTIVE STATUS OF HOCKEY PLAYERS IN THE COURSE OF THEIR TRAINING - Yatsenko, O.V. (World of Medicine and Biology, 2012)
Based on morfometrical quantitative methods developed by the author characteristic features of changes in erythrograms of sportsmen-hockey players have been studied over a 16-week training cycle. It was found that both reactive and adaptive individual features were characterized by a certain range of changes in the "Ehinocytes – Stomatocytes” system. The group assessment revealed quantitative indicators of these changes. The data obtained can be used for the correction of individual physical and stressful loads on the athlete. This will enhance the effectiveness of their performance and the enable prevention of sudden death of an athlete.